Optimisation of cryopreservation technique in Mokara golden nugget orchid using PVS2 vitrification. - Safrinah, R; Xavier, R; Uma Rani, Sinniah; Sreeramanan, S (Academic Journals Inc., 2009)
The study was conducted to evaluate the effects of various sucrose concentrations on Mokara orchid shoots (0.5-1.0 and 1.0-1.5 cm) after precultured at 24 and 48 h. The 1.0-1.5 cm of Mokara shoots preculture at 0.25 M sucrose for 48 h was the best condition based on TTC assay and subsequently used for the following PVS2 vitrification treatment. The selected Mokara orchid shoots were subjected to PVS2 treatment at different time of exposure (min) and temperatures (0 and 24°C). The results showed that viability of shoots reached the highest absorbance value at 10 min and 24°C. However, for the overall treatment with the results shown that 0°C temperature treatment gave the higher absorbance value which could reduce the injurious effects of PVS2. For chlorophyll determination, cryopreservation of shoots at 0°C without LN (LN-) for 5 min exposure to PVS2 recorded as highest chlorophyll content. The result also shows that total chlorophyll a for shoot in all treatment were higher than chlorophyll b.